2009
DOI: 10.1590/s1516-35982009000900025
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de ovelhas da raça Bergamácia alimentadas com dieta contendo gordura protegida

Abstract: RESUMO -Objetivou-se com este trabalho avaliar o efeito do uso de gordura protegida na dieta de ovelhas da raça Bergamácia sobre a produção e composição do leite e a dinâmica de peso das ovelhas. Utilizaram-se 77 ovelhas distribuídas em 2 grupos de forma homogênea por ordem de parição e idade, mantidas com uma dieta controle, com silagem de milho e concentrado, ou com a dieta controle contendo gordura protegida (35 g/ovelha.dia) adicionada ao concentrado. As dietas foram isoenergéticas e isoproteicas e continh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
2
3
0
8
Order By: Relevance
“…On the other hand, Susin (1996) reports the peak between the 3rd and 5th week, while in this research there was no effect of days of lactation on milk production (439.85 mL day −1 ). The peak was observed at 14 days of lactation (496.52 mL day −1 ), close to the values reported by Emediato et al (2009), for Bergamacia sheep, of DI -desaturase index; AI -atherogenicity index; UNSAT/SAT -unsaturated:polyunsaturated fatty acid ratio; CV -coefficient of variation. Cheese yield calculated after 120 ripening days expressed as L of milk/kg of cheese, using the following formula: %Y = (CM/MM) × 100, in which %Y = percentage yield; CM = cheese mass; and MM = milk mass.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, Susin (1996) reports the peak between the 3rd and 5th week, while in this research there was no effect of days of lactation on milk production (439.85 mL day −1 ). The peak was observed at 14 days of lactation (496.52 mL day −1 ), close to the values reported by Emediato et al (2009), for Bergamacia sheep, of DI -desaturase index; AI -atherogenicity index; UNSAT/SAT -unsaturated:polyunsaturated fatty acid ratio; CV -coefficient of variation. Cheese yield calculated after 120 ripening days expressed as L of milk/kg of cheese, using the following formula: %Y = (CM/MM) × 100, in which %Y = percentage yield; CM = cheese mass; and MM = milk mass.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, Emediato et al (2009) evaluated the performance of Bergamácia sheep fed a diet with 16 g crude protein/100 g of diet. These authors reported no weight loss during a 60 day lactation period, with weights of 54.27 and 62.78 kg, immediately after parturition and after 60 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that DMI was possibly not affected by the supply of PF in the concentrate 60 days after lambing, due to the great need for nutrient uptake by lactating ewes. Similar results were observed by Emediato et al (2009b) and Stradiotto et al (2010), who used a supplementation of 35 g PF (Megalac-E) per day in the diet of Bergamácia ewes up to 60 days after parturition. Silva et al (2007) found a decrease in crude protein and lactose and an increase in milk fat levels as PF levels were increased to 6% DM in the concentrate.…”
Section: Coefficient Of Variation In Plots (Supplement)supporting
confidence: 83%
“…In all diets, the body weight of ewes showed a quadratic behavior, with a reduction during the lambing period up to 40 days postpartum, followed by a recovery at the end of the experimental period (Figure 1). Emediato et al (2009a) also observed weight gains for Bergamácia ewes 60 days after postpartum, regardless of the inclusion of PF in the concentrate. For lactating ewes, weight loss is attributed to the difficulty in providing nutrients for feeding in amounts suitable for the matrices during this phase, since the energy demand increases more rapidly than the dry matter intake; therefore, the ewes use energy reservations to produce milk and stop accumulating body mass (Araújo et al, 2008).…”
Section: Coefficient Of Variation In Plots (Supplement)mentioning
confidence: 58%
See 1 more Smart Citation